Dampak Kepercayaan Merek Terhadap Loyalitas Pelanggan : (Studi Kasus Pada Konsumen Hoka Hoka Bento Di Plaza Surabaya) - Ika Sufitri; Sugiharto Sugiharto; Aridha Prassetya; Rina Dewi; Achmad Daengs (Jurnal Pengabdian Masyarakat, 2025)
The development of the business world is getting more rapid, eating the busyness of people's mobility in metropolises will continue to grow. Therefore, people take practical and efficient actions by consuming fast food. Moreover, it is supported by an increase in appetite and higher lifestyle changes. Consumer behavior will affect the way consumers view a product. In determining the brand of the product, it will go through the trial stage first by trying a variety of different products. If it is felt that the brand is suitable and meets what is expected of similar products, then consumers will continue to be loyal or loyal to the brand. This phenomenon is read by Hoka Hoka Bento by using various promotions to save packages and improve quality and service. This study aims to discuss and analyze the influence of brand trust on loyalty in Hoka Hoka Bento customers in Plaza Surabaya.The population in this study is Hoka Hoka Bento consumers who have bought and made repurchases at Hoka Hoka Bento Plaza Surabaya. The sample taken was 110 people. The measuring tools used are questionnaires, as well as data that has been analyzed with simple linear regression